The Relationship of Knowledge with Attitude Adolescent Mental Health - Virgia, Vera; Herlina, Herlina; Wardani, Riska Aprilia (Jurnal Midpro, 2022)
Based on the results of basic health research in 2013 about 2,386,323 adolescents experience emotional mental disorders. Adolescence is a period of transition from childhood to adulthood lasting between 10-19 years during which physical, sexual, and mental changes occur. The purpose of this study is to find out the relationship of knowledge with adolescent mental health attitudes at SMKN Wonosalam. Mental health is an emotional, psychological, and socially healthy state seen from satisfying interpersonal relationships. Effective behavior and coping, positive self-concept, and emotional stability. The methods used are quantitative methods, descriptive design of correlations and cross sectional approaches with stratified random sampling techniques obtained by 169 respondents. The results of the univariate analysis showed that 59.8% of respoden had a good knowledge of mental health and 42% of the respondents' mental health attitudes were negative. The results of bivariate analysis using chi-square showed a knowledge relationship with adolescent mental health attitudes at SMKN Wonosalam (p value 0.018).Keywords: Knowledge, Attitude, Mental Health, Adolescents.Â